Programmable manipulation of zeroth‐order resonance based on an active and digitally coding metamaterial antenna. Issue 20 (1st October 2019) - He, Yiming; Yang, Guangli; Luo, Yong
Abstract : In this Letter, the authors focus on the programmable manipulation in frequency spectrum through an active Metamaterial (MTM) antenna with digitally coding sequences. The MTM cell operates in the zeroth‐order resonance (ZOR) where the resonances are independent of the physical length, providing the freedom to utilise arbitrary cell number with keeping the resonance. Benefiting from the isolated periodical cells, n ‐cell MTM can be tuned by PIN diodes cell by cell individually, hence, achieve many tunable states, which can be coded digitally with sequences, compatible to evolve to programmable functionalities. Micro‐Controller Unit with C Language is utilised to realise programmable voltages for supplying diode switches, resulting in programmable ZOR (PZOR) in one of the 5G band (4.8 to 5.2 GHz), and unfolding the advantages in achieving many NB (Narrow‐Bandwidth) spectrum channels. The proposed programmable MTM ZOR with sliced‐NB channels is suitable for NB‐IoT (Internet of Things) in the near future.